Ecological and environmental risks of heavy metals in sediments in Dingzi Bay, South Yellow Sea. (March 2023) - Liu, Xiaozhu; Sheng, Yanqing; Liu, Qunqun; Li, Zhaoran
Abstract: As a special geographical location between rivers and oceans, coastal estuaries always face severe heavy metal contaminations, especially in semi-closed bay. In this study, the spatial distribution, chemical fraction, ecological risks, and potential sources of heavy metals (Pb, Cr, Cu, As, Cd, Zn, and Ni) in surface sediments and sediment cores were investigated in Dingzi Bay, Shandong Peninsula. The I geo values and modified potential ecological risk index (MRI) indicated that Cd and As presented high environmental risks in the surface and sediment cores. The high concentration sites were mainly located in the middle and the mouth of the Dingzi Bay. The source identification indicated that most heavy metals in surface sediments originated from shipping and aquaculture, while As and Ni from industrial pollution. The correlation coefficients showed that high proportion of fine particle, TN, TOC, TP, and AVS in surface sediments could significantly elevate the bioavailability of most heavy metals. Highlights: Heavy metal contamination risks in sediments in Dingzi Bay were deeply assessed. As and Cd posed higher environmental and ecological risks than other metals. Heavy metals in surface sediments mainly originated from anthropogenic activities.